Design and Development of Interactive Learning Media to Increase Student Learning Interest - Rachmawaty, Rikeu; Sarmidi, Sarmidi; Muhammad, Taofik (Design Journal, 2026)
This study aims to design interactive learning media for improving students' learning interest in computer systems material. The research employs Research and Development (R&D) methodology with the ADDIE development model, encompassing Analysis, Design, Development, Implementation, and Evaluation stages. Seventh-grade students at MTs Ar-Rahmah, Tasikmalaya City, participated as research subjects. Subject matter and media experts validated the interactive learning media, yielding validation results of 100% and 96% respectively, both categorized as "very feasible." Student learning interest effectiveness was measured through questionnaires administered before and after media implementation. Results demonstrated a significant increase in student learning interest following interactive media usage, with an average N-Gain score of 0.70, classified within the high category. The findings indicate that visual displays, animations, and interactive features successfully engaged students and enhanced their participation during learning activities. Statistical analysis confirms the media's capability to address monotonous teaching methods and abstract material challenges. The interactive learning media developed proves both feasible and effective for improving student learning interest in computer systems material, offering a practical solution for educators seeking innovative teaching approaches.